2020
DOI: 10.7202/1074197ar
|View full text |Cite
|
Sign up to set email alerts
|

Les défis de la réinsertion sociale

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Research to date has concentrated on the effect of assistance in particular contexts and has not considered the characteristics of criminal career. Dubois and Ouellet (2020) demonstrated that the challenges of social reintegration vary as a function of the type of offending. For example, individuals having committed sexual offenses face different obstacles than those having committed other types of offences.…”
Section: Current Studymentioning
confidence: 99%
“…Research to date has concentrated on the effect of assistance in particular contexts and has not considered the characteristics of criminal career. Dubois and Ouellet (2020) demonstrated that the challenges of social reintegration vary as a function of the type of offending. For example, individuals having committed sexual offenses face different obstacles than those having committed other types of offences.…”
Section: Current Studymentioning
confidence: 99%